Loss-adjusting: Young People's Constructions of a Future Living With Complex Regional Pain Syndrome. Issue 12 (December 2020) - Jones, Abigail; Caes, Line; Eccleston, Christopher; Noel, Melanie; Rugg, Tessa; Jordan, Abbie
Abstract : Objectives: Complex Regional Pain Syndrome (CRPS) is a chronic pain condition that can present specific difficulties when occurring in adolescence. There is limited work exploring future narratives of healthy adolescents, and how these may differ for those who have chronic health conditions, but there is no research on the future narratives of adolescents who have CRPS. Materials and Methods: In this study, 50 adolescents (44 females, 5 males, 1 preferred not to say) aged 14 to 25 years (mean=19.8, SD=3.68), completed an online story completion task, with a further sample of 10 completing a follow-up telephone interview. Results: Story completion data were initially analyzed deductively based on the work of Morley and colleagues using hoped-for and feared-for future codes, revealing higher instances of hope (291 over 48 stories) than fear (99 over 27 stories). These codes were subsequently analyzed alongside the in-depth interview data using inductive thematic analysis, generating 2 themes that represent distinct, yet related, approaches of how adolescents incorporate CRPS into their future narratives: (1) the centrality of loss theme identifies the ways some adolescents described how CRPS brings loss, with narratives focused on how these adolescents imagine such losses continuing into the future, and (2) the adjusting to loss theme illustrates the ways other adolescents were able to imagine a future in which they were able to adjust to the losses which CRPS may bring. Discussion: CRPS may damage the future plans of adolescents. However, being or learning how to be flexible about these goals, may help them to build more positive future narratives. Abstract : Supplemental Digital Content is available in the text.